Comparing EFL Teachers’ Organizational Integrity and Obligation at Pakistani Universities - Ul Hassan, Mehmood; Abdul Aziz, Asma; Naheed, Asfa (Pakistan Languages and Humanities Review, 2022)
This study was made to have comparison of organizational integrity and organizational obligation among university English teachers in Government Universities of Pakistan. It was deductive study which used survey method for data collection. English teachers of University of Lahore Pakpattan campus, University of Education Vehari, Khwaja Fareed UEIT Rahim Yar Khan, and Bahauddin Zakariya University (henceforth BZU) Multan were selected as sample population for this study. In order to find organizational integrity and obligation among university English teachers of Government Universities, two types of questionnaires were applied, i.e. Organizational Integrity Questionnaire and Organizational Obligation Questionnaire with a reliability of 0.833 and 0.751 respectively. Data were analyzed by ANOVA, Post-hoc Tukey’s test and independent-samples t-test. Results tell that there was well-built observation about organizational integrity and organizational obligation among university English teachers. A factor-wise comparison of organizational obligation and organizational integrity entailed a valuable difference between university English teachers based on gender and ranks. The study suggested recommendations to enforce organizational integrity among universities and measures to boost up obligation among the university English teachers